2018
DOI: 10.1108/srj-01-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

The scantness of the effect of corporate governance mechanisms on executive directors’ remuneration in small listed companies: evidence from Malaysia

Abstract: Purpose This study extensively aims to investigate the effects of different aspects of corporate governance (CG) mechanism, including board size, executive directors’ shareholdings, Chief Executive Officer (CEO) duality, a family member as the CEO and/or chairperson of the board, independent directors in remuneration committee and number of board meeting, on executive directors’ remuneration in small firms listed on Bursa Malaysia (BM). Design/methodology/approach The sample of this study consists of 173 bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 60 publications
1
11
1
Order By: Relevance
“…The use of primary data (questionnaires and interviews) may provide richer data on CG research as it enables researchers to collect more observations, which are unavailable in the annual reports. The present investigation, however, showed that there is a lack of survey research on Malaysian CG (Esa and Ghazali, 2012; Nyambia and Hamdan, 2018; Yusof and Ismail, 2016).…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…The use of primary data (questionnaires and interviews) may provide richer data on CG research as it enables researchers to collect more observations, which are unavailable in the annual reports. The present investigation, however, showed that there is a lack of survey research on Malaysian CG (Esa and Ghazali, 2012; Nyambia and Hamdan, 2018; Yusof and Ismail, 2016).…”
Section: Resultscontrasting
confidence: 60%
“…The only study to use time series data was conducted by Lee and Isa (2015), who concentrated on the financial industry and found that directors’ remuneration is positively associated with board independence and negatively with board size, while CEO duality is not significant. Nyambia and Hamdan (2018) studied the executive remuneration of small firms and found that there is a significant positive relationship between executive ownership, board size and executive remuneration. However, the findings of the existing studies are inconclusive and vary across industries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the coefficient of CEO duality (CEOD) is positive and insignificant. This finding is consistent with the studies by Nyambia and Hamdan (2018) and Haron and Akhtaruddin (2013), which revealed that CEO duality does not influence directors" remuneration. The result for remuneration committee independence (RCIN) shows that the coefficient is negative and not significant, which means that the involvement of independent directors in the remuneration committee does not effects directors" remuneration.…”
Section: Model Specification and Multiple Regression Resultssupporting
confidence: 92%
“…He et al (2018) found that the independence of the nomination committee significantly reduced restatements. The independence of the remuneration committee significantly increases the remuneration of executive directors (Ntim et al, 2019;Nyambia andHamdan, 2018), andNtim et al (2019) also mention that the independence of the nomination and remuneration committee increases payments to the CEO, significantly increasing voluntary executive narrative remuneration action disclosure (Kanapathippillai et al, 2016).…”
Section: 2mentioning
confidence: 99%